Konseptual Pendidikan Merdeka Dalam Transformasi Sistem Pembelajaran Di Indonesia - Astuti, Mardiah; Jumidi Eka Pratama (Indo Publishing, 2026)
Indonesia’s education system is undergoing a significant transformation that requires a learning approach grounded in flexibility, relevance, and the development of 21st-century competencies. The Merdeka Learning framework emerges as a conceptual foundation that places students at the center of the learning process through curriculum flexibility, differentiated instruction, and character reinforcement. This article examines the theoretical foundations, operational principles, and implementation implications of Merdeka Learning within the broader transformation of Indonesia’s educational system. Drawing on constructivist theory, competency-based learning, and ecological perspectives on education, the analysis highlights that successful transformation depends not only on curriculum design but also on the readiness of the entire educational ecosystem. The study concludes that Merdeka Learning has the potential to strengthen educational quality when supported by policy alignment, teacher capacity, and equitable access to learning infrastructure.